Development Of Integrated Lean Six Sigma Model For Small And Medium Enterprise - Ren Jie, Joshua Chan (2017)

(untitled)
Management systems have been developed to guide manufacturers to continuously improve performance in the aspects of quality, cost and delivery. The latest developed management system, Lean Six Sigma (LSS) is an integration of Lean Manufacturing and Six Sigma. Various LSS models have been developed and implemented in different industries with positive and strong evidences. However, literature on developing and implementing LSS models in Small and Medium Enterprise (SME) is scant due to size-related management and resource constraints. This research develop a LSS model named Integrated Lean and Six Sigma tools in DMAIC (ILSSD) model to take into consideration these constraints in the selection of techniques and tools for continuous improvement. The model derives continuous improvement goals from a company’s mission and vision. The ILSSD model consist of DMAIC methodology and proposed collaborated usage of Lean and Six Sigma tools which is not heavy in statistical analysis namely Value Stream Map, Pareto Analysis, Cause and Effect Diagram, Interrelationship Diagram and Tree Diagram. Various data collection techniques were also introduced. The ILSSD model was structured to be data driven so that it provides a decision support system with sound analysis. The practicality of ILSSD was validated in an SME label printing company and SME semiconductor company in Penang. The results of implementation are 18.42% reduction in setup time in label printing company and 92.8% reduction in waiting time in semiconductor company. The research has achieved its objectives.